Interleukin-17 in Liver Disease Pathogenesis - Li, Na; Yamamoto, Gen; Fuji, Hiroaki; Kisseleva, Tatiana (Seminars in Liver Disease, 2021)
Interleukin 17A (IL-17A)-producing T helper 17 (Th17) cells were identified as a subset of T helper cells that play a critical role in host defense against bacterial and fungal pathogens. Th17 cells differentiate from Th0 naïve T-cells in response to transforming growth factor β1 (TGF-β1) and IL-6, the cytokines which also drive development of liver fibrosis, require activation of transcription factor retinoic acid receptor-related orphan nuclear receptor gamma t (RORγt). IL-17A signals through the ubiquitously expressed receptor IL-17RA. Expression of IL-17RA is upregulated in patients with hepatitis B virus/hepatitis C virus (HBV/HCV) infections, nonalcoholic steatohepatitis (NASH), alcohol-associated liver disease (AALD), hepatocellular carcinoma (HCC), and experimental models of chronic toxic liver injury. The role of IL-17 signaling in the pathogenesis of NASH- and AALD-induced metabolic liver injury and HCC will be the focus of this review. The role of IL-17A–IL-17RA axis in mediation of the cross-talk between metabolically injured hepatic macrophages, hepatocytes, and fibrogenic myofibroblasts will be discussed.
Keywords: IL-17 signaling; metabolic syndrome; lipogenesis; TNF signaling